Zakat Profesi Sebagai Distribusi Pendapatan Ekonomi Islam - Muhammad Zen (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
In today's modern economy, there is no doubt that the distribution is the most important sector in economic activity. Included in the Islamic economic perspective, the study of income distribution of profession zakat attract serious attention from Muslim economists because it has an important role for the welfare of society. The teachings of Islam called on every Muslim who has an income property that in their property threre are rights of others that must be fulfilled / distributed. Property income that is distributed to charity will positively impact the welfare of society in the islamic economic dimension.